Beginning Perl - Poe, Curtis (Wiley, 2012)
Everything beginners need to start programming with Perl Perl is the ever-popular, flexible, open source programming language that has been called the programmers' Swiss army knife. This book introduces Perl to both new programmers and experienced ones who are looking to learn a new language. In the tradition of the popular Wrox Beginning guides, it presents step-by-step guidance in getting started, a host of try-it-out exercises, real-world examples, and everything necessary for a Perl novice to start programming with confidence. * Introduces Perl to both new programmers and experienced ones who want to learn a new language * Provides a host of real-world applications for today's environments so readers can get started immediately * Covers the new features of Perl but fully applicable to previous editions Beginning Perl provides the information and instruction you need to confidently get started with Perl. For Instructors: Classroom and training support material are available for this book.